Some Reflections on the Annual Report of the Council of Economic Advisers - Hansen, Alvin H. (The Review of Economics and Statistics, 1962)
to study policies affecting money and credit separately from fiscal policy, because the underlying cause-effect relations are so very different. In terms of a summary characterization of the new budget, what I have tried to convey is this: Let us not say that it is designed to show the impact of economic policies; let us rather say more modestly that it shows the impact of fiscal policies; and let us make clear that a detailed and comprehensive analysis of monetary and credit policies cannot be conducted within the framework of the NIP accounts.